Purchasing Behaviour and Problems Faced by Farmers in the Adoption of Biostimulants in Selected Talukas of Kutch District, Gujarat, India - , Dhruv N. Patoliya, Dilip R. Vahoniya, Bhavesh A. Dodiya (Archives of Current Research International, 2025)
The study explores the purchasing behaviour and challenges faced by farmers in the adoption of biostimulants in four talukas of Kutch district, Gujarat, Nakhatrana, Bhuj, Bhachau, and Mandvi. Primary data were collected from 200 purposively selected farmers through structured interviews conducted over a 60-day period. Results showed that 48 percent of farmers were between 36 and 50 years of age, and 36 percent had only primary-level education. Most respondents (60%) practiced farming as their primary occupation, and 48 percent had annual incomes between ₹1-5 lakh. The analysis using Weighted Average Mean revealed that price (WAM: 4.715) and past experience (WAM: 4.366) were the most significant factors influencing purchasing decisions, followed by product quality (WAM: 3.980). Availability (WAM: 2.066) and peer suggestions (WAM: 2.385) had the least influence. Garrett Ranking analysis highlighted major constraints in adoption, with high price (WAM: 2.655), delayed effect (WAM: 2.535), and uncertainty (WAM: 2.160) being top barriers. The study concludes that although biostimulants hold great potential for promoting sustainable agriculture, their adoption remains constrained by affordability, knowledge gaps, and market availability. Strengthening farmer education, providing price support, and ensuring timely access through improved supply chains are essential to enhance adoption levels across the region.